2014
DOI: 10.1021/je500205z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Surface Properties and Solubility of 1-Vinyl-3-alkyl/Esterimidazolium Halide Ionic Liquids by Density Functional Methods

Abstract: A series of 1-vinyl-3-alkylimidazolium halide ([VRIM]X) and 1-vinyl-3-esterimidazolium chloride ([VEIM]-Cl) ionic liquids, a functional material with unsaturated bonds, were synthesized by using microwave-assisted synthesis method. The structures were characterized by 1 H NMR. Through Gaussian09/B3PW91/6-311G (2d,p) density functional methods, the interaction energies of ion pairs of [VRIM]X and [VEIM]Cl were obtained. The relationships between the surface tensions and temperature (293.15 to 333.15) K, molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Because magnetism of the MILs interferes with the measuring signal, only 1 H NMR spectra for the intermediate ILs were measured. As can be seen from the data in Table , the results demonstrated that the synthetic compounds were [VRIM]­Br, [VRIM]­Cl, and [VEIM]­Cl …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Because magnetism of the MILs interferes with the measuring signal, only 1 H NMR spectra for the intermediate ILs were measured. As can be seen from the data in Table , the results demonstrated that the synthetic compounds were [VRIM]­Br, [VRIM]­Cl, and [VEIM]­Cl …”
Section: Resultsmentioning
confidence: 97%
“…According to Scheme a, other intermediate ILs were synthesized adopting the route of [VBIM]­Br . On the basis of the results of 1 H NMR spectra, the mass fraction purity for the liquid ILs is >0.980, and for the solid ILs is >0.990 . The intermediate ILs are summarized in Table .…”
Section: Experimental Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three reasons can cause the increase of the solubility of the title complex in acetone. In the three reasons, the first one has been verified [24][25]. By the comparison with the As seen in Table 3, the solubility of the complex in chloroform is higher than that in ethyl acetate.…”
Section: Solubility Of [Co(vim) 4 ](Ncs)mentioning
confidence: 94%
“…The carbon atom on the imidazolium ring is between two nitrogen atoms, which makes the carbon atom have part of positive charge ( +δ C-H), thus, the interaction between the carbon atom and the carbonyl oxygen (C=O δ-) becomes easier [24][25]. Secondly, due to the active hydrogen on the -CH 3 of acetone and the presence of abundant acetone in the solution, the hydrogen bond interaction (S…H) between NCS -and the active hydrogen on the imidazolium ring can exist.…”
Section: Solubility Of [Co(vim) 4 ](Ncs)mentioning
confidence: 99%